2014
DOI: 10.1086/674967
|View full text |Cite
|
Sign up to set email alerts
|

Moving beyond species–discharge relationships to a flow-mediated, macroecological theory of fish species richness

Abstract: Hydrologic indices can be used in macroecological models of fish species richness. I used fish distributions and river flow records from 89 river basins in the Pacific Northwest (USA) to identify robust associations between aspects of flow and fish species richness. I calculated 148 hydrologic indices for each basin, created single-predictor regression models for each hydrologic index, and tested for significant relationships between native fish species richness and specific components of flow. I used multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 54 publications
(62 reference statements)
2
18
0
Order By: Relevance
“…This study adds to the growing recognition that Q , as an indicator of the space or habitat available to aquatic organisms, is a key predictor of freshwater community structure and biodiversity (e.g. Oberdorff et al ., ; Poff & Allan, ; Guégan et al ., ; Iwasaki et al ., ; McGarvey, ). Our hemispheric‐scale SDR results were remarkably similar to the global‐scale SDR models of Oberdorff et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This study adds to the growing recognition that Q , as an indicator of the space or habitat available to aquatic organisms, is a key predictor of freshwater community structure and biodiversity (e.g. Oberdorff et al ., ; Poff & Allan, ; Guégan et al ., ; Iwasaki et al ., ; McGarvey, ). Our hemispheric‐scale SDR results were remarkably similar to the global‐scale SDR models of Oberdorff et al .…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of rivers in the U.S. Pacific Northwest found that native fish richness is more strongly associated with low flow Q than with mean annual Q or high flow Q (McGarvey, ). We observed a similar result in our more extensive study of Western Hemisphere rivers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Iwasaki et al. () found that their best regression model included both mean discharge and flow variability measures while McGarvey's () best model included only discharge variability measures. Nonetheless, McGarvey and de Freitas Terra () concluded that discharge appeared as a strong predictor of freshwater fish richness in the Americas because it integrated the effects of climate and catchment size, rather than directly determining richness.…”
Section: Introductionmentioning
confidence: 99%